The basics of construction of jet-drop optical systems for measuring the electric field strength. Part 1 - E. V. Leun (Омский научный вестник)
The article discusses the principles and possibilities of using jet-drop optical measuring systems for monitoring the electric field strength (EFS). Two applied techniques are considered. First, the deflection of flying charged droplets (balls, hollow granules) used as micro-objects sensitive to EFS and deviating from a given rectilinear trajectory of motion, like an electron in a kinescope. Secondly, stroboscopic determination of the position and/or displacement of drops by pulsed illumination of the side of the deflected drop by the optical flow and measurement of the reflection angle for it. The possibilities of implementing the differential method of EFS measurements are discussed. The features of the use of liquids with the addition of metal nanopowders or based on liquid metals, as well as hollow droplets in the form of microspheres or hollow granules are considered.